Pengembangan Media ROTARKAT (Roda Berputar Pakaian Adat) Pada Materi Keberagaman Pakaian Adat di Indonesia Untuk Pembelajaran IPS Kelas IV di Sekolah Dasar - Anggraeni, Aprida; Arya Setya Nugroho (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Based on the results of observations and interviews with homeroom teachers at UPT SD Negeri 12 Gresik there were several problems including the media used was still very weak because it was limited and lacked variety. Educators in conveying material only race on thematic books and limited learning media, namely in the form of posters, pictures, atlas books, maps, and globes so that they can influence the learning process of students by causing several problems, namely students still find it difficult to understand the content of the material , students are often sleepy, bored and play alone with their friends so they don't focus on participating in learning. This study aims to produce ROTARKAT (Traditional Clothing Rotating Wheel) media. The method used in this research is the 4-D development model which is modified into 3-D which consists of 3 stages only, namely: Define, Design, and Develop. Subjects in this study were 12 students. Data collection techniques and instruments used in this study were validation sheets and student response questionnaires. The learning media ROTARKAT (Traditional Clothing Rotating Wheel) has gone through several stages of media expert validation and material expert validation with the final result of media validity obtaining an average score of 94.8% and 97.5% in the "very valid" category. So it can be concluded that the ROTARKAT media (Traditional clothing Rotating Wheel) can be used in the learning process. Keywords: ROTARKAT Learning Media; 4-D Model; Validity.